The Effect of Implementing Problem Based Learning in Lesson Study on Students Critical Thinking Skills - Ernanda, Melania; Suharsono, Suharsono; Triyanto, Samuel Agus (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
This study aims to investigate the effect of implementing problem-based learning in lesson study on students' critical thinking skills, especially of the topic human respiratory system. The research method used is a true experiment with a posttest-only control design. The population in this study were students of class XI MIPA SMAN 1 Tasikmalaya which consisted of 8 classes with a total number of students was 273. The samples used in this study were 2 classes, class XI MIPA 8 an experimental class with 35 students, and class XI MIPA 7 a control class with 33 students. The sampling technique was carried out by cluster random sampling technique. Data collection techniques in the form of critical skills test a total of 15 things. The instrument is used to test critical thinking skills on the material of the human respiratory system. The data analysis technique was carried out by using a t-test. The results significance value is 0.023<0.05 can be said that there is an effect of problem-based learning models on students' critical thinking skills in the human respiratory system